2008
DOI: 10.1111/j.1744-7917.2008.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) biotype Q based on mitochondrial DNA markers

Abstract: In the present study, genetic differentiation of Bemisia tabaci (Gennadius) biotype Q was analyzed based on mitochondrial cytochrome oxidase I (mt COI) gene sequence. The results showed that B. tabaci biotype Q could be separated into two subclades, which were labeled as subclades Q1 and Q2. Subclade Q1 was probably indigenous to the regions around the Mediterranean area and subclade Q2 to Israel or Cyprus. It was because B. tabaci was composed of several genetically distinct groups with a strong geographical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 42 publications
(50 reference statements)
6
55
0
1
Order By: Relevance
“…There were significant differences in allelic richness between populations ( F 12,72 = 2.26, P = 0.02). Populations from the New World (including biotype A) and biotype S had the lowest number of alleles, while the invasive biotypes B and Q (West and East Med refer to subclades Q1 and Q2 respectively as per Chu et al [84]) had an intermediate number of alleles. The highest number of alleles was observed in the Yemen population, the presumed closest relative of biotype B represented in the dataset, and in populations from Sub-Saharan West and North and West Africa that is the presumed closest relatives of biotype Q sister clade represented herein (Fig 1, Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were significant differences in allelic richness between populations ( F 12,72 = 2.26, P = 0.02). Populations from the New World (including biotype A) and biotype S had the lowest number of alleles, while the invasive biotypes B and Q (West and East Med refer to subclades Q1 and Q2 respectively as per Chu et al [84]) had an intermediate number of alleles. The highest number of alleles was observed in the Yemen population, the presumed closest relative of biotype B represented in the dataset, and in populations from Sub-Saharan West and North and West Africa that is the presumed closest relatives of biotype Q sister clade represented herein (Fig 1, Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Within the Q biotype clade there was a obvious split into two sister genetic groups originating from the eastern Mediterranean (including the Israel-Q) and those sampled from the western Mediterranean (including the Spanish-Q), a genetic split also evident based on the mtCOI data [84]. The Eastern Mediterranean Q cluster was more structured than the West Mediterranean Q and comprised well-differentiated populations that included those from Cyprus, Greece, Israel, and Turkey, whereas, there was evidence of more gene flow within the Western Mediterranean group that included those from Spain, Morocco, France, Canary Islands, and a population introduced to China.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From their native regions, both biotypes have spread all over the world because of the trade of the host plants; they have colonized the invasion areas and have displaced less-injurious indigenous populations (Brown 2007) because of their superior adaptability to environments highly disturbed by agricultural practices (Delatte et al 2009), asymmetric mating interactions Crowder et al 2010) and indirect vector-virus mutualism via host plants (Jiu et al 2007). Recent studies have shown a considerable genetic variability amongst mitochondrial lineages of biotype Q. Phylogenetic analysis of COI haplotypes revealed the occurrence of two widespread subgroups, Q1 (western Mediterranean populations) and Q2 (eastern Mediterranean populations), both of which have spread to not native geographic areas (Tsagkarakou et al 2007;Chu et al 2008;Ahmed et al 2009), and two more groups, namely, Q3, consisting of populations from Burkina Faso only, besides ASL (Africa silverleafing) consisting of Sub-Saharan populations only (Gueguen et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…The other two genetic variants, named Q3 and ASL (Africa silverleaÞng), consist of populations from Burkina Faso only and from Sub-Saharan Africa, respectively (Gueguen et al 2010). Both Q1 and Q2 have been found in the United States and in Mediterranean countries like Spain and France (Chu et al 2008, Ahmed et al 2009, Mouton et al 2012. Recently, in a greenhouse area of southern Italy, the frequency of Q2 whiteßies has been found to largely exceed that of Q1 whiteßies on intensive greenhouse tomato crops showing strong symptoms of tomato yellow leaf curl disease (Parrella et al 2013).…”
mentioning
confidence: 97%